2000
DOI: 10.1128/iai.68.7.4084-4091.2000
|View full text |Cite
|
Sign up to set email alerts
|

High Intracellular Level of Guanosine Tetraphosphate in Mycobacterium smegmatis Changes the Morphology of the Bacterium

Abstract: Almost one-third of the world population today harbors the tubercle bacillus asymptomatically. It is postulated that the morphology and staining pattern of the long-term persistors are different from those of actively growing culture. Interestingly, it has been found that the morphology and staining pattern of the starved in vitro population of mycobacteria is similar to the persistors obtained from the lung lesions. In order to delineate the biochemical characteristics of starved mycobacteria, Mycobacteria sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 42 publications
1
87
0
1
Order By: Relevance
“…A modified method described previously was used to examine bacterial morphology (Ojha et al, 2000;Steel et al, 2004). B. abortus wild-type, the spoT mutant and the complemented strain were cultured in Brucella broth at 37 uC for 24 h to ensure full growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified method described previously was used to examine bacterial morphology (Ojha et al, 2000;Steel et al, 2004). B. abortus wild-type, the spoT mutant and the complemented strain were cultured in Brucella broth at 37 uC for 24 h to ensure full growth.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have reported that the stringent response is associated with morphological changes and physiological adjustment. High levels of ppGpp cause a morphological change in Mycobacterium smegmatis (Ojha et al, 2000). ppGpp acts as a second messenger to co-ordinate virulence expression as an adaptive response to amino acid starvation in Legionella pneumophila (Hammer & Swanson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Legionella pneumophila, (p)ppGpp triggers a switch between the avirulent replicative phase and the virulent motile phase (Hammer & Swanson, 1999), while in M. tuberculosis, (p)ppGpp accumulation is important for the transition into latency (Ojha et al, 2000;Primm et al, 2000). In addition, the expression of specific virulence genes has been shown to be modified by RelA: in Vibrio cholerae, inactivation of RelA results in decreased expression of cholera toxin and the toxin-coregulated pilus (Haralalka et al, 2003), and a Salmonella enterica spoT/relA mutant has reduced expression of HilA, the central regulator of the Salmonella pathogenicity island (SPI) 1 and SPI 2 virulence genes (Pizarro-Cerda & Tedin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nutritionally starved bacteria have been demonstrated to bear significant similarity with the natural persistors (Nyka, 1974). In fact, an in vitro starvation model has led to the discovery of at least two genes, sigF (Chen et al, 2000) and relA\spoT (Primm et al, 2000 ;Ojha et al, 2000) which are involved in the long term persistence of Mycobacterium tuberculosis. With an objective of gaining further insight into the physiological changes that occur during nutritional starvation in mycobacteria, we have studied the change in the profile of cell surface biologically active lipid, glycopeptidolipid (GPL), of Mycobacterium smegmatis in response to carbon starvation.…”
Section: Introductionmentioning
confidence: 99%